Abandoned Mines – Categories in Romanian Local Newspapers - People and Places - Chefneux Gabriela (Bulletin of Transilvania University, 2023)
The paper uses the Matrix Categorization Devices theory in order to analyze the way in which the abandoned mines in Romania have been presented in newspapers over the period beginning with their closure up to the present time. In order to conduct the analysis, the paper provides a theoretical framework of the Membership Categorization Device (the category being mines and the members – the people and places); the last part discusses the results of the analysis.